Preferensi Masyarakat Terhadap Kriteria Perancangan Ruang Komunitas - Nurulhijah, Nelfi Rifma (Universitas muhammadiyah palembang, 2023)
The nature humans as social beings need each other to survive and cause interactions in them. Social interactions can form specific communities or groups. In a community, people need space to move. Therefore, this study aims to determine community preferences regarding the choice of community gathering places to consider community space design criteria. Using exploratory qualitative methods with a grounded theory approach in this study is expected to produce data by selecting criteria for community places. Data analysis used four stages, namely open coding, axial coding, selective coding, and distribution analysis to determine the level of answers from participants. The results of the study found that in designing a place or community space, three design criteria could be used, including the concept of space, spatial planning, and the character and atmosphere of the space.